Training for Better Management: Avante Zambézia, PEPFAR and Improving the Quality of Administrative Services; Comment on "Implementation of a Health Management Mentoring Program: Year-1 Evaluation of Its Impact on Health System Strengthening in Zambézia Province, Mozambique" - Sandra K. Schwarcz; George W. Rutherford; Hacsi Horvath (Kerman University of Medical Sciences, 2015)
The United States President's Emergency Plan for AIDS Relief (PEPFAR) emphasizes health systems strengthening as a cornerstone of programmatic success. Health systems strengthening, among other things, includes effective capacity building for clinical care, administrative management and public health practice. Avante Zambéziais a district-level in-service training program for administrative staff. It is associated with improved accounting practices and human resources and transportation management but not monitoring and evaluation. We discuss other examples of successful administrative training programs that vary in the proportion of time that is spent learning on the job and the proportion of time spent in classrooms. We suggest that these programs be more rigorously evaluated so that lessons learned can be generalized to other countries and regions.